Răspuns :
1. √8 · (√3 - 2) - 5√6 + √50 =
=2√2(√3 - 2) - 5√6 + 5√2 =
=2√6 - 4√2 - 5√6 + 5√2 =-3√6 + √2
2. ( - √2 ) · ( -√3 ) + 2√54 - √24 =
= √6 + 6√6 - 2√6 =5√6
3. [ √3 · (2√27 + √6 ) + √2 ] : 2 - √8 =
=[ √3 · (6√3 + √6 ) + √2 ] : 2 - 2√2 =
=( 18 + √18 + √2 ) : 2 - 2√2 =
=( 18 + 3√2 + √2 ) : 2 - 2√2 =
=(18+4√2):2-2√2=
=9+2√2-2√2=9
=2√2(√3 - 2) - 5√6 + 5√2 =
=2√6 - 4√2 - 5√6 + 5√2 =-3√6 + √2
2. ( - √2 ) · ( -√3 ) + 2√54 - √24 =
= √6 + 6√6 - 2√6 =5√6
3. [ √3 · (2√27 + √6 ) + √2 ] : 2 - √8 =
=[ √3 · (6√3 + √6 ) + √2 ] : 2 - 2√2 =
=( 18 + √18 + √2 ) : 2 - 2√2 =
=( 18 + 3√2 + √2 ) : 2 - 2√2 =
=(18+4√2):2-2√2=
=9+2√2-2√2=9
1. √8 · (√3 - 2) - 5√6 + √50 =
= √24 - 2√8 - 5√6 + √50
= 2√6 - 4√2 - 5√6 + 5√2
= -3√6 + √2
2. ( - √2 ) · ( -√3 ) + 2√54 - √24 =
= 1√6 + 6√6 - 2√6
= 7√6 - 2√6
= 5√6
3. [ √3 · (2√27 + √6 ) + √2 ] : 2 - √8 =
= mie la acesta nu imi da 9 ci 13 - 2√2...
o sa mai incerc...daca imi iasa o sa iti scriu rezolvarea...sper ca te-am ajutat cu 1 si 2
= (6√9 + √18 + √2) : 2 - 2√2
= (18 + 3√2 + √2) :2 - 2√2
= (18 + 4√2) · 1/2 - 2√2
= (18/2 + 4√2/2) - 2√2
= 9 + 2√2 -2√2
= 9.
= √24 - 2√8 - 5√6 + √50
= 2√6 - 4√2 - 5√6 + 5√2
= -3√6 + √2
2. ( - √2 ) · ( -√3 ) + 2√54 - √24 =
= 1√6 + 6√6 - 2√6
= 7√6 - 2√6
= 5√6
3. [ √3 · (2√27 + √6 ) + √2 ] : 2 - √8 =
= mie la acesta nu imi da 9 ci 13 - 2√2...
o sa mai incerc...daca imi iasa o sa iti scriu rezolvarea...sper ca te-am ajutat cu 1 si 2
= (6√9 + √18 + √2) : 2 - 2√2
= (18 + 3√2 + √2) :2 - 2√2
= (18 + 4√2) · 1/2 - 2√2
= (18/2 + 4√2/2) - 2√2
= 9 + 2√2 -2√2
= 9.